2011
DOI: 10.1089/gtmb.2010.0057
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate Reductase Polymorphisms C677T and A1298C as Maternal Risk Factors for Down Syndrome in Jordan

Abstract: There is strong association between MTHFRC677T and maternal risk of DS in Jordanian mothers younger than 35 years old and the MTHFR1298C allele has a lesser but additive risk effect in MTHFR677T/1298C compound heterozygotes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Various studies have shown that the C677T polymorphism is a maternal risk factor for DS [40][41][42][43][44]. However, there are few studies in patients with DS per se, as has been evaluated in our present study.…”
Section: Discussionmentioning
confidence: 83%
“…Various studies have shown that the C677T polymorphism is a maternal risk factor for DS [40][41][42][43][44]. However, there are few studies in patients with DS per se, as has been evaluated in our present study.…”
Section: Discussionmentioning
confidence: 83%
“…There have also been studies in Brazil (7,12,17) and a few studies in Arab populations, such as in the United Arab Emirates (6), Egypt (13) or Jordan (16). Very few studies have been conducted in Caucasian populations and Europe; only in Italy (8,10,22), Turkey (20,24), and Croatia (24).…”
Section: Discussionmentioning
confidence: 99%
“…Folate deficiency and deficiency of donors of methyl groups at the cellular level are both associated with abnormal methylation in DNA, chromosomal instability, rupture of DNA chains, aberrant chromosomal recombination, abnormal chromosome segregation, and meiotic nondisjunction of chromosomes and aneuploidies (1,4,5). A hypothesis has been advanced that genitors of patients with trisomy 21 (MIM *156570), and consequently possess altered metabolism of folate and homocysteine (2)(3)(4)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Another hypothesis states the involvement of other genes, such as methylenetetrahydrofolate dehydrogenase (5,19).…”
Section: Introductionmentioning
confidence: 99%
“…Since the study by James et al (1999), polymorphisms in the MTHFR gene are the most frequently investigated in attempt to clarify the role of folate and methyl metabolism in the maternal risk for DS (Martínez-Frías et al, 2008). Several studies have associated the MTHFR 677CT polymorphism and the risk of bearing a child with DS (da Silva et al, 2005;Meguid et al, 2008;Sadiq et al, 2011;Wang et al, 2008) as well as with increasing plasma Hcy concentration (P.M. Biselli et al, 2007;da Silva et al, 2005;Narayanan et al, 2004;Ulvik et al, 2007). Another common polymorphism in the MTHFR gene, the substitution of alanine for cytosine at the 1298 position, was already associated with DS risk and increased plasma Hcy concentration (Martínez-Frías et al, 2006;Meguid et al, 2008;Narayanan et al, 2004, Rai et al, 2006Scala et al, 2006;Weisberg et al, 2001).…”
Section: Folate Metabolism Genomic Stability and Maternal Risk For mentioning
confidence: 99%
“…In addition to the MTHFR gene, other genetic polymorphisms involved in the folate pathway seem to modulate the maternal risk for bearing a child with DS (Bosco et al, 2003;J.M. Biselli et al, 2008a;Meguid et al, 2008;Pozzi et al, 2009;Sadiq et al, 2011;Scala et al, 2006;Wang et al, 2008) as well as the concentrations of metabolites involved in the folate pathway (Ananth et al 2007;Barbosa et al, 2008;Cheng et al, 2010;Devos et al, 2008). The MTR 2756 A→G polymorphism has been associated with increased maternal risk for DS in the presence of AG or GG genotypes, as well as when combined with polymorphisms MTRR 66 A→G (MTR 2756AG/MTRR 66AG) (Bosco et al, 2003) and MTHFR 677 C→T (MTHFR 677TT/MTR 2756AA).…”
Section: Folate Metabolism Genomic Stability and Maternal Risk For mentioning
confidence: 99%